2014
DOI: 10.1186/1475-2875-13-278
|View full text |Cite
|
Sign up to set email alerts
|

DDX39B (BAT1), TNF and IL6 gene polymorphisms and association with clinical outcomes of patients with Plasmodium vivax malaria

Abstract: BackgroundDDX39B (BAT1) encodes an RNA helicase known to regulate expression of TNF and IL-6. Elevated levels of these two cytokines are associated with increased severity of clinical malaria. The aim of this study was to investigate the relationship between single nucleotide polymorphisms (SNPs) in the DDX39B, TNF and IL6 genes and the clinical outcomes of patients with Plasmodium vivax malaria.MethodsCross-sectional investigations were carried out in two regions of the Brazilian Amazon where several studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 54 publications
(55 reference statements)
2
30
0
Order By: Relevance
“…Contradictory results were observed for malaria, with the TNFA-308A allele associated with higher susceptibility/severity [6264], without alterations [39] or with resistance to P. falciparum malaria [65]. Regarding vivax malaria, which was the focus of the present study, our results were in agreement with other studies, including those in the Brazilian Amazon that did not observe any associations between the TNFA-308G>A SNP and susceptibility or clinical manifestations due to P. vivax infection [10, 19, 66]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Contradictory results were observed for malaria, with the TNFA-308A allele associated with higher susceptibility/severity [6264], without alterations [39] or with resistance to P. falciparum malaria [65]. Regarding vivax malaria, which was the focus of the present study, our results were in agreement with other studies, including those in the Brazilian Amazon that did not observe any associations between the TNFA-308G>A SNP and susceptibility or clinical manifestations due to P. vivax infection [10, 19, 66]. …”
Section: Discussionsupporting
confidence: 91%
“…One hypothesis for the lack of association of the evaluated SNPs is that malaria can occur due to possible linkage disequilibrium of the SNPs in TNFA with the human leukocyte antigens (HLAs), which can cause nonfunctional mutations [65, 66]. The A allele (-308) is described as having a strong linkage disequilibrium with HLA-Bw53 and DRB1 ∗ 1302-DQB1 ∗ 0501, whereas the A allele at the -238 position of the TNFA gene appears to be linked to HLA-B53 but with different immune characteristics [62].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic and or paucisymptomatic infections by P. falciparum and Plasmodium vivax were detected in epidemiological studies in the states of Rondônia (RO) and Amazonas, which likely indicates a pattern of clinical immunity in both populations. [24][25][26][27][28] Seropidemiological studies investigating the type of immune responses elicited in naturally exposed populations to several malaria vaccine candidates in Brazilian populations provide important information on whether immune responses specific to these antigens are generated in natural infections and their immunogenic potential as vaccine candidates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Gnjec et al reported that the -23 GG genotype of BAT1 -23 C/G was associated with reduced risk of Alzheimer's disease in Caucasian population (OR = 0.43) 23 . On the other hand, Mendonça et al reported in patients infected with Plasmodium vivax that the -23 G allele was associated with reduced clinical manifestations of malaria in Brazilian populations 14 .…”
Section: Discussionmentioning
confidence: 98%
“…The BAT1, NFKBIL1, and LTA genes are located in the 6p21.3 region. BAT1 encodes a nuclear protein is called HLA-B-associated transcript 1, which negatively regulates the expression of interleukin (IL)-1, tumor necrosis factor (TNF), and IL-6 13,14 ; NFKBIL1 encodes a protein homologous to IκB (κB inhibitors), which regulates the expression of nuclear factor-kappa B transcription factor, TNF, IL-1, and IL-6 15 ; and LTA encodes a protein involved in the inflammatory and immunological response 16 . LTA binds to their cognates, TNF receptors (TNFR1) and TNFR2, and regulates the expression of anti-apoptotic proteins to prevent cell death, inflammatory response, and cell differentiation 17 .…”
Section: Introductionmentioning
confidence: 99%